2003
DOI: 10.1016/s0735-1097(03)00243-2
|View full text |Cite
|
Sign up to set email alerts
|

C-reactive protein, clinical presentation, and ischemic activity in patients with chest pain and normal coronary angiograms

Abstract: The hs-CRP correlates with symptoms and ECG markers of myocardial ischemia in CPNCA patients. Whether hs-CRP is related to the pathogenesis of angina in these patients deserves further investigation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
85
2
3

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 141 publications
(92 citation statements)
references
References 21 publications
2
85
2
3
Order By: Relevance
“…Veleska et al could not find any relationship between serum hs-CRP levels and exercise testing results in a study that included 200 patients with positive exercise tests 8. On the other hand, Cosin-Sales et al reported a correlation between serum hs-CRP levels and ST-segment depression during exercise testing with Holter monitoring, and the frequency of angina episodes in patients with typical chest pain and normal coronary angiograms 6. Therefore, the relationship between hs-CRP and reversible myocardial ischaemia was not as clear as in unstable coronary artery disease and needs to be clarified in large-scale studies.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Veleska et al could not find any relationship between serum hs-CRP levels and exercise testing results in a study that included 200 patients with positive exercise tests 8. On the other hand, Cosin-Sales et al reported a correlation between serum hs-CRP levels and ST-segment depression during exercise testing with Holter monitoring, and the frequency of angina episodes in patients with typical chest pain and normal coronary angiograms 6. Therefore, the relationship between hs-CRP and reversible myocardial ischaemia was not as clear as in unstable coronary artery disease and needs to be clarified in large-scale studies.…”
Section: Discussionmentioning
confidence: 98%
“…However, its role in predicting transient myocardial ischaemia in stable coronary heart disease is not clear. While some studies found a strong relationship between serum hs-CRP levels and reversible myocardial ischaemia in exercise electrocardiographic testing,6 others did not find such a relationship 7,8…”
Section: Discussionmentioning
confidence: 98%
“…Anjiyografik olarak normal koronerleri ve reversibl miyokardiyal kanlanma defekti olan bireylerde iskemi sırasında endoteliyal disfonksiyon ve transmiyokardiyal laktat üretimi izlenmiştir (27). İskemi sırasında hsCRP düzeylerinin arttığı görülmüştür (13). İskemiyi takip eden reperfüzyon sonrasında kısa bir sürede (yaklaşık 15 dakika) serbest oksijen radikallerinin oluşumu, kompleman sistem aktivasyonu, koroner endoteline nötrofil tutunması ve IL-6 ve IL-1 gibi akut proinflamatuvar sitokinlerin aktive olduğu deneysel çalışmalarda gösterilmiştir (28 arasında pozitif korelasyon olduğunu göstermişlerdir.…”
Section: Discussionunclassified
“…4,12,14) More recently, chronic inflammation was found to be associated with cardiac syndrome X. 15,16) The evidence for this was the elevated inflammatory markers associated with the disease activity and the effect of statin, a lipid-lowering as well as anti-inflammatory drug, which has significantly modified the disease process in cardiac syndrome X. [17][18][19] CRP is the prototypic acute phase reactant and marker of inflammation.…”
Section: Discussionmentioning
confidence: 99%